Quantitative Estimation of Aspirin Using Hydrotropic Solubilization Technique - Maheshwari, R.K.; Aher, R.; Wanare, G.; Jagwani, Y.; Kapoor, Ankita; Joshi, Anshu; Khandelwal, Aditi (Asian Journal of Chemistry, 2010)
In the present study, 2 M sodium salicylate solution has been employed to solubilize a poorly water-soluble drug, aspirin for its titrimetric analysis in tablets. Results of analysis by proposed methods were comparable with those of standard British Pharmacopoeial method. Results of analysis have been validated statistically. The proposed method is quicker than Pharmacopoeial method with its novelity, simplicity, accuracy and reproducibility.